Mechanics in neuronal development and repair - Franze, Kristian; Janmey, Paul A.; Guck, Jochen (Annual Review of Biomedical Engineering, 2013)
Biological cells are well known to respond to a multitude of chemical signals. In the nervous system, chemical signaling has been shown to be crucially involved in development, normal functioning, and disorders of neurons and glial cells. However, there are an increasing number of studies showing that these cells also respond to mechanical cues. Here, we summarize current knowledge about the mechanical properties of nervous tissue and its building blocks, review recent progress in methodology and understanding of cellular mechanosensitivity in the nervous system, and provide an outlook on the implications of neuromechanics for future developments in biomedical engineering to aid overcoming some of the most devastating and currently incurable CNS pathologies such as spinal cord injuries and multiple sclerosis. Copyright © 2013 by Annual Reviews.
CRIS-Team Scopus Importer:2020-08-12
Keywords: brain; glial cells; mechanosensitivity; neurons; stiffness; viscoelasticity